2001
DOI: 10.1354/vp.38-2-143
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evidence for Effects of Magnesium Supplementation on Quinolone-treated Horse and Dog Chondrocytes

Abstract: Quinolones and magnesium deficiency cause similar lesions in joint cartilage of young animals. Chondrocytes cultivated in the presence of quinolones and in Mg-free medium show severe alterations in cytoskeleton and decreased ability to adhere to the culture dish. We investigated whether Mg2+ supplementation can prevent quinolone-mediated effects on chondrocytes in vitro. Chondrocytes cultivated in Dulbecco's modified Eagle's medium/HAM's F-12 medium were treated with ciprofloxacin (80 and 160 microg/ml) and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 25 publications
4
27
0
5
Order By: Relevance
“…This agrees with the study which observed that Ciprofloxacin inhibits tendon cell proliferation and cause cell cycle arrest in rats (Tsai et al, 2008). It was reported that cell proliferation in horse and dog chondrocytes decreased in Ciprofloxacin cultivated groups (Egerbacher et al, 2001).…”
Section: Ajptsupporting
confidence: 92%
“…This agrees with the study which observed that Ciprofloxacin inhibits tendon cell proliferation and cause cell cycle arrest in rats (Tsai et al, 2008). It was reported that cell proliferation in horse and dog chondrocytes decreased in Ciprofloxacin cultivated groups (Egerbacher et al, 2001).…”
Section: Ajptsupporting
confidence: 92%
“…NMDA receptor antagonists have been shown to effectively alleviate pain-related behavior in animal models as well as in clinical situations [17,18]. The safety of IA magnesium sulfate was tested in an unpublished animal study conducted on rats and then in an in vitro animal study conducted by Egerbacher et al [19], and no side effects were detected.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have also been confirmed in the chondrocytes of juvenile rats 39 . On the other hand, supplementation with magnesium can reduce the toxic effects of quinolones on chondrocytes in vitro 40 .…”
Section: Cavity Formationmentioning
confidence: 99%